Dynamic corporate liquidity - Nikolov, Boris; Schmid, Lukas; Steri, Roberto (Journal of Financial Economics, 2019)
In contrast to cash holdings, credit lines give firms financial flexibility by providing liquidity contingent on realized funding needs, but they are often limited by collateral and covenants. We embed this trade-off into an estimated dynamic model of financing and investment. Our model highlights the relevance of drawing down credit lines to fund investment options in an effective way and quantitatively matches well the levels and dynamics of cash, credit lines, and leverage. In the cross-section, modeling credit lines as contingent liquidity provides novel empirical predictions and rationalizes several stylized facts regarding credit line usage, covenant violations, and cash holdings.